COMPARATIVE ANALYSIS OF WALLS’ SOUNDPROOFING IN RESIDENTIAL BUILDINGS: MATERIALS’ PERFORMANCE ON AIRBORNE SOUND INSULATION - Rakhat Namanov (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This thesis investigates how well various wall systems in residential buildings can reduce airborne sound. The study centers on clay bricks, autoclaved aerated concrete blocks, and lightweight expanded clay blocks. Moreover, it examines how pairing these materials with different kinds of plasterboards and various densities of mineral wool affects their soundproofing effectiveness. A comparative experimental approach was used to determine the Sound Transmission Class (STC) of different wall layouts using standardized protocols. The results show that combining high-density mineral wool and superior acoustic plasterboards with traditional wall materials significantly improves sound insulation, surpassing the legal requirement. The findings offer valuable insights for architects and construction experts aiming to improve acoustic comfort in city residential structures. To promote sustainable soundproofing solutions, the research identifies practical limitations and proposes directions for future investigations. Additionally, the study highlights real-life challenges and provides suggestions for upcoming research to enhance eco-friendly soundproofing methods.
Keywords: type of access: embargo; Acoustic comfort; Sound insulation; Building materials; Noise pollution